Relevansi Kebijakan Kenaikan Usia Pernikahan terhadap Kesiapan Berkeluarga: Analisis Pemikiran Prof. Nasaruddin Umar - Nila Fadllilatul Husna (Tadabbur: Jurnal Integrasi Keilmuan, 2025)
The amendment to the Indonesian Marriage Law through Law Number 16 of 2019, which raised the minimum marriage age to 19 years, was intended to strengthen child protection and promote marital readiness. Nevertheless, the policy has shown limited effectiveness in fostering substantive marriage readiness and long-term family resilience because it primarily emphasizes chronological age while paying insufficient attention to psychological, social, economic, and spiritual preparedness. This study aims to examine Prof. Nasaruddin Umar's concept of the "11 Proactive Mediation Strategies" as an alternative framework for strengthening family resilience. Employing a qualitative library research design with content analysis and hermeneutic approaches, the study analyzes the concept through the perspectives of Progressive Law and Maqashid al-Shariah. The findings reveal that Nasaruddin Umar proposes a multidimensional model of marital readiness that integrates legal, psychological, social, economic, and spiritual dimensions through a tiered mediation system consisting of prevention, early intervention, and post-divorce assistance. This study contributes an integrative framework that bridges state legal policy with the substantive objectives of Islamic law, thereby offering a preventive and holistic approach to strengthening family resilience in contemporary Indonesia.